Using Video Editing Tools for Teaching Purposes - Wood, Robert (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Most sociology instructors find film an important medium in their teaching. But effectiveuse of film may be constrained by the playback projection equipment in the classroom and by the fact that potentially useful films may be too long or contain too much extraneous material to be employed in classroom settings. This brief article explores how the use of video editing tools can assist instructors in overcoming these and other problems.